Peningkatan Motivasi dan Hasil Belajar Menemukan Gagasan Utama Paragraf Melalui Teknik Pembelajaran SQCP bagi Peserta Didik Kelas IX-B SMP Negeri 1 Jaken Semester Genap Tahun 2014/2015 - Suladi, Slamet (widiyanto, 2015)
The outline for this PTK are how the learning process occur, enhancing learning motivation and enhancing study outcome at finding prime idea of students of 1 Jaken Junior High School class IX-B with SQCP learning technique. The research implementation occur in two cycles. The outcame of research: the learning process of SQCP technique run smoothly, learning motivation of students improve as the SQCP technique is applied, and the average of school grades from cycles I to cycles II are increasing to 4,59. The attainment of students from first cycle to second cycle increase to 20,83%.